The pyramidal syndrome and the pyramidal tract: a brief historical note - Rezende-Cunha,Fernando (2011)
The discovery of the pyramidal syndrome and tract is briefly reviewed with emphasis on a few key historical aspects. The pursuit of the relationship between the lateralized deficits resulting from contralateral head trauma begins in the fourth century BC with the Hippocratic School and continues until the present day.